Phonemic Training Modulates Early Speech Processing in Pre-reading Children - Bauch, Anne; Friedrich, Claudia K.; Schild, Ulrike (Frontiers in Psychology, 2021)
Phonemic awareness and rudimentary grapheme knowledge concurrently develop in preschool age. In a training study, we tried to disentangle the role of both precursor functions of reading for spoken word recognition. Two groups of children exercised with phonemic materials, but only one of both groups learnt corresponding letters to trained phonemes. A control group exercised finger-number associations (non-linguistic training). After the training, we tested how sensitive children were to prime-target variation in word onset priming. A group of young adults took part in the same experiment to provide data from experienced readers. While decision latencies to the targets suggested fine-grained spoken word processing in all groups, event-related potentials (ERPs) indicated that both phonemic training groups processed phonemic variation in more detail than the non-linguistic training group and young adults at early stages of speech processing. Our results indicate temporal plasticity of implicit speech processing in preschool age as a function of explicit phonemic training.